Potential Impact of Climate Change on Agricultural Productivity: A Cross Country Analysis - Soni, Deepa; Kohli, Anju (Productivity, 2024)
Climate change is a spontaneous process which can be observed over a longer duration of time - around ten to fifteen years. It refers to long-term shifts in temperatures and weather patterns. Climate variation has been identified as the major cause of year-to-year fluctuations in agricultural production in both developed and developing countries. The present paper investigates the impact of climate change on agricultural productivity by employing the stochastic frontier production function proposed by Battese and Coelli (1995) with time varying effect using panel data spanning from 1995 to 2022 for four leading agricultural countries - Brazil, China, India and US. The stochastic frontier production function is based on the Cobb-Douglas production function in which agricultural output is regressed on various inputs along with the climate parameter to capture the technical efficiency effects involved in production function. The estimated results suggest that there is a significant negative impact of climate change on agricultural production as well as its technical efficiency. The correlation results also indicate that climate change has a detrimental impact on agricultural output as well as labour productivity. There is need for policies that jointly address sustainable development and climate change. Three broad categories of action are required - cutting emissions, adapting to climate change and financing for required adjustments. Alternative development pathways such as pursuing institutional changes and stimulating clean technology innovations can affect climate change. While excessive government intervention is inadvisable, if climate change is left unchecked, it will be a drag on the economy.
Keywords: Agricultural Productivity; Climate Change; Agriculture